Health economic evaluation of a web-based intervention for depression: The EVIDENT-trial, a randomized controlled study - Viola Gräfe; Thomas Berger; Martin Hautzinger; Fritz Hohagen; Wolfgang Lutz; Björn Meyer; Steffen Moritz; Matthias Rose; Johanna Schröder; Christina Späth; Jan Philipp Klein; Wolfgang Greiner (Health Economics Review, 2019)
Background: Depression often remains undiagnosed or treated inadequately. Web-based interventions for depression may improve accessibility of treatment and reduce disease-related costs. This study aimed to examine the potential of the web-based cognitive behavioral intervention 'deprexis' in reducing disease-related costs. Methods: Participants with mild to moderate depressive symptoms were recruited and randomized to either a 12- week web-based intervention (deprexis) in addition to care as usual (intervention group) or care as usual (control group). Outcome measures were health-related resource use, use of medication and incapacity to work as well as relating direct health care costs. Outcomes were assessed on patients' self-report at baseline, three months and six months. Results: A total of 1013 participants were randomized. In both groups total direct health care costs decreased during the study period, but changes from baseline did not significantly differ between study groups. Numeric differences between study groups existed in outpatient treatment costs. They could be attributed to differences in changes of costs for psychotherapeutic treatment from baseline. Whereas costs for psychotherapeutic treatment decreased in the intervention group, costs increased in the control group (- 16.8% ( exteuro80) vs. + 14.7% ( exteuro60)) (tdf = 685 = 2.57; p = 0.008). Conclusion: The study indicates the health economic potential of innovative e-mental-health programs. There is evidence to suggest that the use of deprexis over a period of 12 weeks leads to a decrease in outpatient treatment cost, especially in those related to different types of psychotherapeutic treatment.
Keywords: 330; Economic issues; Outcome studies; Health economic evaluation; E-mental-health; Deprexis; Depression; Randomized controlled trial